The wandering throne of Solomon: objects and tales of kingship in the medieval Mediterranean - Iafrate, Allegra (Mediterranean art histories, 2016)
In 'The wandering throne of Solomon: Objects and tales of kingship in the medieval Mediterranean' Allegra Iafrate analyzes the circulation of artifacts and literary traditions related to king Solomon, particularly among Christians, Jews and Muslims, from the 10th to the 13th century.00The author shows how written sources and objects of striking visual impact interact and describes the efforts to match the literary echoes of past wonders with new mirabilia. Using the throne of Solomon as a case-study, she evokes a context where Jewish rabbis, Byzantine rulers, Muslim ambassadors, Christian sovereigns and bishops all seem to share a common imagery in art, technology and kingship